CAYC - Circulars. (Buenos Aires : Centro de arte y communicación, 1975)
Borges, Jorge Luis ; Tocci, Mirta ; Borla, Hector ; etc.
The CAYC, Buenos Aires is organizing a circulating show called "The Decade of the 70's"
boek